A comparison of finalists to semi-finalists in the 50 m swimming events at the 9th FINA World Swimming Championships Fukuoka 2001 - Ikuta, Y.; Okuno, K.; Ogita, F.; Takagi, H.; Wakayoshi, K.; Nomura, T.; Miyashita, M. (Biomechanics and Medicine in Swimming IX, 2003)
The purpose of this study was to compare the swimming performances between finalists and semifinalists in 50 m events at the 9th FINA World Swimming Championships FUKUOKA 2001. RESULTS Finalists were faster than semifinalists in the record and the time taken to perform each phase for all events. Significant difference between finalists and semifinalists were found in the record. In the starting phase, there were significant differences between finalists and semifinalists in freestyle and butterfly for men and breaststroke and butterfly for women. In the 1st swimming phase, finalists for the men`s freestyle were significantly faster than semifinalists. In contrast, there were significant differences between finalists and semifinalists in the other events except the men`s freestyle. For the men`s butterfly, the women`s freestyle and breaststroke, finalists were significantly faster than semifinalists in the finish phase. These results were evident that there was not a common tendency from the comparison between finalists and semifinalists in 50 m events. However, it was suggested that the 1st half of the swimming race for the men`s freestyle and the 2nd swimming phase for all but the men`s freestyle were very important in the semifinal races to be qualified as the finalist of 50 m events for the world top level swimmers.